Avaliação do desempenho de cultivares de alface em cultivo hidropônico e panorama da hidroponia no Estado do Espírito Santo - Galon, Karla (2012)
Few studies on the behavior of the lettuce in hydroponic culture in Brazil, mainly in tropical environment, have led many producers to choose cultivars with no scientific background and safety statistics, resulting in economic losses. The objective of thi